Dacomitinib for Advanced Non-small Cell Lung Cancer Patients Harboring Major Uncommon EGFR Alterations: A Dual-Center, Single-Arm, Ambispective Cohort Study in China - Li, Hong-Shuai; Yang, Guang-Jian; Cai, Yi; Li, Jun-Ling; Xu, Hai-Yan; Zhang, Tao; Zhou, Li-Qiang; Wang, Yu-Ying; Wang, Jin-Liang; Hu, Xing-Sheng; Yan, Xiang; Wang, Yan (Frontiers in Pharmacology, 2022)
Dacomitinib is a standard first-line option in NSCLC patients with classic epidermal growth factor receptor (EGFR) mutations. However, clinical evidence of dacomitinib activity against uncommon mutations in non-small cell lung cancer (NSCLC) is currently limited. In this ambispective study, we aimed to evaluate the efficacy and safety of dacomitinib in patients with NSCLC harboring major uncommon EGFR mutations in a relatively large scale. Thirty-two patients harboring major uncommon EGFR mutations received dacomitinib monotherapy. This study found that dacomitinib is well-tolerated and effective in patients with advanced NSCLC harboring major uncommon EGFR mutations, and it also has favorable activity for brain metastases in this setting.